1989
DOI: 10.1113/jphysiol.1989.sp017519
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mesencephalic nucleus and trigeminal ganglion mechanoreceptors in the periodontal ligament of the cat.

Abstract: 1. In anaesthetized cats recordings have been made in the mesencephalic nucleus of the fifth cranial nerve and the trigeminal ganglion from neurones that respond when forces are applied to the mandibular canine tooth. The site of the mechanoreceptors in the periodontal ligament and their distribution around the tooth root have been determined. 2. Receptors with their cell bodies in the mesencephalic nucleus were found to be situated in the periodontal ligament in a discrete area intermediate between the fulcru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Electrophysiological studies have demonstrated that the cell bodies of these mechanoreceptors are found in two anatomically distinct sites: the mesencephalic nucleus of the fifth cranial nerve Correspondence to: B. Millar and the trigeminal ganglion (for review see Linden 1990). Linden and Scott (1989) located mechanoreceptors in the ligament itself and recorded from the cell bodies in the two sites. They showed that there was a difference in the distribution, within the periodontal ligament of the mandibular canine tooth, between the mechanoreceptors with their cell bodies in the mesencephalic nucleus and those with their cell bodies in the trigeminal ganglion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological studies have demonstrated that the cell bodies of these mechanoreceptors are found in two anatomically distinct sites: the mesencephalic nucleus of the fifth cranial nerve Correspondence to: B. Millar and the trigeminal ganglion (for review see Linden 1990). Linden and Scott (1989) located mechanoreceptors in the ligament itself and recorded from the cell bodies in the two sites. They showed that there was a difference in the distribution, within the periodontal ligament of the mandibular canine tooth, between the mechanoreceptors with their cell bodies in the mesencephalic nucleus and those with their cell bodies in the trigeminal ganglion.…”
Section: Introductionmentioning
confidence: 99%
“…The two groups of periodontal ligament mechanoreceptors have different cell body locations, a different distribution of receptor position in the periodontal ligament, and a different range of response properties (see Linden and Scott 1989). In view of these differences, there is the possibility that the nerve endings may be morphologically different.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown different distribution of MS and TG receptors in PDL of cat. Distribution of mechanoreceptors were found to be homogeneous and heterogeneous in the middle and apical portion of cat's tooth with their soma in TG and MS respectively [92]. Authors agreed by and large that periodontal ligament have two types of mechanoreceptors, rapidly adapting and slowly adapting.…”
Section: Periodontium and Proprioceptionmentioning
confidence: 80%
“…[92] 1989 Suggests that periodontal receptors remains in the bone even after tooth extraction contributing to osseoperception…”
Section: Author Year Theorymentioning
confidence: 99%
“…Other studies have shown that a high proportion of mechanosensitive units with cell bodies in the mesencephalic nucleus are maximally sensitive to distolingually directed forces (Linden & Scott, 1989). It has been suggested that periodontal mechanoreceptors respond maximally when the area of ligament in which they are situated is under tension (Cash & Linden, 1982 b).…”
mentioning
confidence: 99%